Self-Evolving Cognitive Environments for Autonomous Robotics: A Closed-Loop Learning Architecture for Adaptive Physical Systems - Akangsha Sunil Bedmutha (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Today's autonomous robotic systems are designed to work under heavy architecture constraints․ Although they are well-suited for static assumptions about the environment, most use cases, be it in warehouses, transportation systems, manufacturing, or shared spaces, require robots to be able to adapt to fixed or slowly changing environments. Self-Evolving Cognitive Environments (SECE), on the other hand, relies on system-level architectural advances, wherein the robotic agents, the physical environments, and the artificial intelligence systems function as a single closed-loop system wherein learning is not confined to the agent only but can extend to co-adaptation of the environment dynamics and the agent's behaviors through perception, behavioral modeling, and policy experimentation. This involves a six-layer architecture wherein multi-modal perception, environmental state representation, behavior modeling, closed-loop experimentation, policy learning, and edge-cloud orchestration are tightly interlinked and allow the environment to adapt and improve the operational policy online in the physical environment, rather than relying on offline training in simulated environments. A range of applications (including those in warehouse logistics, autonomous driving, delivery robots, and industrial robotics) shows how system-level learning can lead to strong, scalable, contextual autonomy through the co-adaptation of the environment and the agent as a foundational building block towards capabilities that were previously out of reach for autonomous agents. DOI: https://doi.org/10.17762/ijisae.v14i1s.8233